Accounting Students' Perceptions of The Ethics of Preparing Financial Statements - Nursari, Oktavia Winda; Boedi, Soelistijono; Nastiti, Rizky; Syaefuddin, Syaefuddin; Akbar, Masithah (Asosiasi Dosen Akuntansi Indonesia, 2023)
This study aims to determine the students' perceptions of the role of understanding ethics in shaping student ethics and to find out the students' perceptions of making financial statements in meeting the needs of financial statement users. The research sample was determined using the Slovin formula to obtain 100 respondents, consisting of 41 undergraduate accounting students of STIE Indonesia Banjarmasin and 59 undergraduate accounting students of Lambung Mangkurat University. The results of this study indicate significant differences in perceptions of earnings management, misstatements, and cost benefits to users of financial statements. Meanwhile, the differences in perceptions regarding disclosing sensitive information and accountability to financial statement users are insignificant.